P-289 Oxygen and fire safety in a hospice setting: a collaborative approach to change practice. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - McGarr, Doug; Jenkinson, Rebecca
Abstract : Background: Following on from the tragic events at Grenfell Tower and attending an ECLiHP UK conference presentation entitled 'Supporting staff through a traumatic event in the workplace', Clinical and Estates Leads worked together to facilitate positive change Aims: Educate all staff and volunteers in safe procedures for fire and oxygen safety by creating a three-hour fire safety workshop unique to our hospice. Making sure that policies and procedures that were going to be controversial were discussed openly in a safe environment with time allowed for feedback. Method: Clinical and Estates Leads working collaboratively to design a bespoke workshop suitable for clinical and non–clinical roles and ensuring all staff received quality training with a variety of teaching methods used to produce clear outcomes Updated policies for fire evacuation, oxygen awareness and smoking, using the workshops as a vehicle to roll these out to staff for feedback before final agreement with senior managers and trustees Created a working group of colleagues from departments across the hospice to develop a new referral form to identify if a patient is a smoker prior to admission, produce a risk assessment for patients who smoke and leaflets for service users, one for smoking and one for safe use of oxygen. Results: Clinical, non–clinical staff and volunteers provided with consistent and bespoke on–site fire safety workshops rolled out to over 150 staff and volunteers New policies agreed and implemented for smoking, fire safety and medical gases. Conclusion: In 12 months we have facilitated 20 fire safety workshops, updated policies and implemented new documents and ways of working with excellent feedback received, putting the safety and welfare of patients, visitors and our workforce at the forefront of what we do. Plans are in place to facilitate refresher training for all staff next year.